PERANAN BADAN NARKOTIKA NASIONAL PROVINSI RIAU DALAM PEMBERANTASAN PEREDARAN NARKOTIKA DI LAPAS KELAS II.A PEKANBARU DIKAITKAN DENGAN UPAYA PEMBINAAN. - Desi Silvia Angraini; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Development Correctional Institution, a very strategic position in realizing the ultimate goal of the criminal justice system is rehabilitation and social reintegration of law violators. The purpose of implementing the Corrections system to make the Citizens Correction of Corrections to be full human beings, being aware of the error to recover themselves and not to repeat the criminal act that can be received by the community may Actively participate in development and can normal life as a good citizen and responsible Although the function of the Correctional System is a corrective set Citizens' patronage healthy to integrate with the community so that it can play a role as a member of the community Society, that is free and responsible. Nevertheless, the goal and function of prisons does not seem to be achieved, as evidenced by the drug trafficking in prisons II.A class Pekanbaru.The purpose of this dissertation, namely: First, the Riau Provincial Narcotics Bureau to combat drug drivers to determine in prison II.A Class Pekanbaru, second, to cause the major drug trafficking trapped in prisons II.A Class Pekanbaru, Third, to determine the function of Pekanbaru Penitentiary II.A class in the field of guidance of prisoners related to narcotics in prison PekanbaruII.Aclass. This type of research is used in writing this law is a legal research sosilogis. By using juridical research sociological (empirical jurisprudence research) to find empirical studies of theories about the process and about the functioning of the law in society.The research has three key conclusions. First of all, the role of the National Narcotics Bureau of the Province of Riau in the fight against drug traffickers in prisons II.A Class Pekanbaru is to make everything work in order to profess narcotics in prisons II.A Class Pekanbaru insurmountable. Second, Causes Circulation of Narcotics in Prisons II.A Class Pekanbaru caused by three factors, namely the economic factors, failure factors, Factor dependence. Third, Judicial Institutions In the field of coaching, a block of rehabilitation has been opened for prisoners who tested positively on drugs. Saran author, First, to monitor the Riau BNNP drug problem again in prisons. Secondly, the prison security system needs to be fixed again. Third party prisons should be more active in performing the rehabilitation block.Keywords: Penitentiary-Circulation-Narcotics-BNNP Riau